Evaluasi Risiko Kesehatan dan Keselamatan Kerja dengan Metode Hirarc pada Proyek Pembangunan Sistem Penyediaan Air Baku Bendungan Pengga Kabupaten Lombok Tengah - Muhammad Daud; Muhammad Arief Budihardjo; R Rizal Isnanto (Universitas Diponegoro, 2023)
AbstractThe construction of Pengga Dam bulk water supply system in Central Lombok district has considerable complexity that requires health and safety risk evaluation management, that include part of the project plan and control. This construction consist of several working stage: intake work, jetty work, galvanized pipe connection work, HDPE pipe connection work and pipe bridge construction work. This study uses HIRARC (Hazard Identification Risk Assessment and Risk Control) method consisting of risk identification, risk assessment, and risk control. Risk assessment is explored through field observations and job supervision. Result of the study identifies risks on 7 working stages in which there are any identified potential hazards with multi-levels of risk, in which are low risk, medium risk, up to high risk level. The hazard risk is caused by the absence of occupational safety and health training, inadequate work methods and equipment, the absence of safety signs and complete standardized PPE, also the absence of supervision carried out by the job executor. Risk control should be undertaken in the form of administrating Standard Operating Procedure (SOP) and appropriate use of PPE when carrying out job activities and when in site. Keywords: Hazard Identification Risk Assessment and Risk Control, Bulk Water